MANAJEMEN PERUBAHAN DAN PENGEMBANGAN DI PT. JASAMARGA CABANG BELMERA Tbk.(Studi Kasus Pengelolaan PT. JASAMARGA CABANG BELMERA Tbk.) - Muhammad Fauzan; Chuzaimah Batubara (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Companies operating in a constantly changing environment must be able to manage change well in order to remain relevant and competitive. PT. Jasamarga Belmera Branch Tbk. (Jasamarga Belmera) is a company engaged in toll road management services in Indonesia. In facing industrial developments and increasingly complex market demands, Jasamarga Belmera needs to implement effective change and development management to achieve its business objectives. This abstract discusses the change management and development practices implemented by PT. Jasamarga Belmera Branch Tbk. in dealing with company and industry dynamics